ELASTIC PROPERTIES OF FORSTERITE-ENSTATITE COMPOSITES UP TO 3.0 GPA - Ji S.; Wang Z. (My University, 1999)
Which rule of mixture is the best for predicting the overall elastic properties ofpolyphase rocks based on the elasticities and volume fractions of their constituents? In order toaddress this question, we sintered forsterite-enstatite polycrystalline aggregates with a variedforsterite volume fraction (0, 0.2, 0.4, 0.5, 0.6, 0.8 and 1.0). Elastic properties of thesesynthesized composites were measured as a function of pressure up to 3.0 GPa in aliquid-medium piston cylinder apparatus using a high precision ultrasonic interferometrictechnique. The experimental data can be much better described by the shear-lag model than bythe commonly used simple models such as Voigt, Reuss and Hill averages, Hashin-Shtrikmanbounds, Ravichandran bounds, Halpin-Tsai equations, and Pauls calculations. We interpret thisas an indication that the elastic interaction and stress transfer between phases are neglected in allmodels except the shear-lag model. In particular, the present study suggests that olivine in themantle may be more abundant than previously inferred from the comparison between seismicEarth model velocities and calculated overall elastic properties of mantle mineral compositesaccording to the Hill average or Hashin-Shtrikman bounds.